2008
DOI: 10.1097/ico.0b013e318169d698
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet A/Riboflavin Corneal Cross-linking for Infectious Keratitis Associated With Corneal Melts

Abstract: Purpose: To evaluate the efficacy of ultraviolet-corneal crosslinking (CXL) for treating infectious melting keratitis.Methods: Five patients with infectious keratitis associated with corneal melting were treated with CXL at the outpatient departments of the Institut für Refraktive und Ophthalmo-Chirurgie and the eye hospital at the University of Zurich. CXL was performed when the infection did not respond to systemic and topical antibiotic therapy. Follow-up after cross-linking ranged from 1 to 9 months.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
207
0
21

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 290 publications
(235 citation statements)
references
References 18 publications
7
207
0
21
Order By: Relevance
“…Furthermore, UV radiation itself can damage both DNA and RNA of pathogens and is used as an antimicrobial procedure 22. Recently, CXL with the interaction of riboflavin and UV irradiation was reported to also be used in corneal infections 23, 24, 25. After the topical application of riboflavin and UVA light, the reaction causes the release of very reactive singlet oxygen and other reactive oxygen radicals, which leads to apoptosis of, for example, keratocytes in the cornea 26, 27, 28.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, UV radiation itself can damage both DNA and RNA of pathogens and is used as an antimicrobial procedure 22. Recently, CXL with the interaction of riboflavin and UV irradiation was reported to also be used in corneal infections 23, 24, 25. After the topical application of riboflavin and UVA light, the reaction causes the release of very reactive singlet oxygen and other reactive oxygen radicals, which leads to apoptosis of, for example, keratocytes in the cornea 26, 27, 28.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that therapeutic transplants represent 2.6% to 17.9% of total penetrating transplants (17) . There are reports of corneal ulcers treated successfully with corneal collagen crosslinking (CXL) (18)(19)(20)(21)(22)(23)(24)(25) . An experimental study found increased resistance to enzymatic digestion by collagenase, pepsin, and trypsin in corneas subjected to CXL (26) .…”
mentioning
confidence: 99%
“…Riboflavin and ultraviolet-A (UVA)-induced crosslinking of corneal collagen (CXL) is a method to increase the biomechanical [1][2][3][4] and biochemical 5,6 stability of the cornea by inducing additional crosslinks within or between collagen fibers using UVA light and the photomediator riboflavin. The therapeutic potential of CXL to treat progressive keratoconus was demonstrated in a clinical pilot study, 3 as well as in controlled prospective studies and in case reports and case series of patients with iatrogenic keratectasia after refractive laser surgery.…”
mentioning
confidence: 99%